THE EFFECTS OF DYNAMIC URBAN DEVELOPMENT OF CARRYING CAPACITY OF AGRICULTURE LAND IN NORTHERN COAST OF WEST JAVA - EKA PRAJA (NIM : 25414028), ZULYASMAN
North Coast area of West Java is an area that has a high economic value, so the development is very fast. The development trend of urban that goes expansive and sprawl, essentially/basically led to the discontinuation of the urban environment as indicated by a decrease in the carrying capacity of the environment. This study aims to assess the influence of the dynamics of urban development and its impact on the carrying capacity of agricultural land, with a case study in the North Coast Region of West Java. The scope of this research area is the North Beach area of West Java, which consists of Bekasi City, Cirebon City, Bekasi District, Karawang District, Subang District, Indramayu District and Cirebon District. The unit of analysis is the administrative area sub-districts. Data that used are statistics from BPS City/Regency in periode of 2009-2015. This type of research is descriptive quantitative research, by analyzing the rate of developed land growth, the rate of population growth and economic growth. Then the results of the analysis views its association with the status of the carrying capacity of the land, with a variable rate of depreciation of agricultural land. The linkage of variables and variable dynamics of urban development land capacity using multiple regression analysis and overlay analysis. Based on the analysis of land capacity of 2014 there are 41 sub-districts with surplus status and 130 sub-districts with a deficit status. The linkage dynamics of urban development on land capacity by using multiple regression analysis, the most influential variable is Population Growth Rate by value of -2.11%. The linkage dynamics of urban development on the carrying capacity of land by using overlay analysis, pattern with a level of high consistency with variable dynamics of urban areas with a high category and a variable rate of depreciation of agriculture land with high category located in the Sub-District Tegalwaru, Sub-District Purwasari, Sub-District Tirtamulya, and Sub-District Kota Baru ( District Karawang).